2010
DOI: 10.1785/0120080194
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Broadband Ground-Motion Simulations: Combining Long-Period Deterministic Synthetics with High-Frequency Multiple S-to-S Backscattering

Abstract: We present a new approach for computing broadband (0-10 Hz) synthetic seismograms by combining high-frequency (HF) scattering with low-frequency (LF) deterministic seismograms, considering finite-fault earthquake rupture models embedded in 3D earth structure. Site-specific HF-scattering Green's functions for a heterogeneous medium with uniformly distributed random isotropic scatterers are convolved with a source-time function that characterizes the temporal evolution of the rupture process. These scatterograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 51 publications
0
96
0
Order By: Relevance
“…In source studies, removing the attenuation term is fundamental in order to study self-similarity of the source spectrum; this can be done by inverting for the theoretical Q , using empirical Green's functions (EGFs) or multiple EGFs to remove path and site effects, measuring spectral parameters from the coda, or using κ r to correct for high-frequency attenuation (e.g., Irikura, 1986;Abercrombie, 1995;Mayeda and Walter, 1996;Hough, 1997;Lancieri et al, 2012). In the generation of synthetic ground motion using point-source or finite-fault stochastic or hybrid simulation approaches, κ 0 is applied as a low-pass filter to constrain high frequencies, affecting peak ground motion and spectral shape (Boore, 1986;Beresnev and Atkinson,2005;Mai et al, 2010;Schmedes et al, 2010;Foster et al, 2012), imposing such a constraint is necessary to achieve realistic results at high frequencies. The amount of the κ correction in such approaches depends on how Q is incorporated in the TGFs.…”
Section: κ: a Multitude Of Applications Physical Interpretations Anmentioning
confidence: 99%
“…In source studies, removing the attenuation term is fundamental in order to study self-similarity of the source spectrum; this can be done by inverting for the theoretical Q , using empirical Green's functions (EGFs) or multiple EGFs to remove path and site effects, measuring spectral parameters from the coda, or using κ r to correct for high-frequency attenuation (e.g., Irikura, 1986;Abercrombie, 1995;Mayeda and Walter, 1996;Hough, 1997;Lancieri et al, 2012). In the generation of synthetic ground motion using point-source or finite-fault stochastic or hybrid simulation approaches, κ 0 is applied as a low-pass filter to constrain high frequencies, affecting peak ground motion and spectral shape (Boore, 1986;Beresnev and Atkinson,2005;Mai et al, 2010;Schmedes et al, 2010;Foster et al, 2012), imposing such a constraint is necessary to achieve realistic results at high frequencies. The amount of the κ correction in such approaches depends on how Q is incorporated in the TGFs.…”
Section: κ: a Multitude Of Applications Physical Interpretations Anmentioning
confidence: 99%
“…Today, interest in κ 0 is renewed because it constitutes an important input parameter when adjusting GMPEs to different regions through the host-to-target method (Cotton et al 2006;Douglas et al 2006;Biro & Renault 2012) and in constraining high frequencies for synthetic ground motion generated either by stochastic, physics-based, or hybrid-method simulations (e.g. Boore 2003; Graves & Pitarka 2010;Mai et al 2010). The latest generation of GMPEs is also expected to incorporate κ 0 as a new predictor variable (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of near-field recordings hampers the development of a complete understanding of the physical causes of ground-motion variability. Therefore, physicsbased simulation techniques that include a specified but complex rupture processes and wave-propagation effects are used to compute and analyze near-field ground motion and its variability (e.g., Spudich and Frazer, 1984;Komatitsch and Tromp, 1999;Dumbser and Kaeser, 2006;Mai et al, 2010). Ripperger et al (2008) showed that the azimuthal dependence of interevent ground-motion variability is strongest in the backward-directivity region.…”
Section: Introductionmentioning
confidence: 99%